The benefits and costs of group affiliation: Evidence from East Asia - Stijn Claessens; Joseph P.H. Fan; Larry H. P. Lang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper investigates the benefits and associated agency costs of using internal capital markets through affiliating with groups using data of two thousand firms from nine East Asian economies between 1994-6. We find that mature and slow-growing firms with ownership structures more likely to create agency problems gain more from group affiliation, while young and high-growth firms more likely lose. Agency problems are important explanatory factors of firm value in economies outside Japan, but less so in Japan. Consistent with the literature, financially constrained firms benefit from group affiliation. Our results are robust to different time periods and estimation techniques.
Keywords: G32; G34; L22; 330; business group; group affiliation; East Asian corporations; Wertpapieremission; Eigentümerstruktur; Organschaft; Ostasien